(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study examined the determinants of household food security among small ruminant farmers in Osun State, Nigeria. A cross-sectional survey design was adopted, and a multi-stage sampling technique was used to select 286 respondents. Data were collected using structured interview schedules and analyzed using descriptive statistics, Pearson correlation, multiple regression, and analysis of variance (ANOVA). Results revealed that about 70% of households experienced varying degrees of food insecurity. Socio-economic characteristics such as education, income, flock size, and farming experience had significant positive effects on household food security, while household size had a negative effect. Economic security indicators, including income, asset ownership, and income diversification, showed strong positive relationships with food security. The ANOVA results further indicated significant differences in food security across agricultural zones. The study concludes that improving income, livestock productivity, and access to resources is essential for enhancing household food security. It recommends improved access to credit, strengthened extension services, and support for income diversification among small ruminant farmers.